Meningkatkan Kompetensi Karier Mahasiswa melalui Fleksibelitas Kebijakan Pertukaran Internal Lintas Program Studi - Pande Ketut Ratih Widhiadyani; Komang Sri Widiantari; I Made Suidarma (Universitas Teuku Umar, 2025)
Improving student career competency is a key focus that is increasingly being intensified in higher education. A policy that can support the flexibility to achieve this goal is through student exchanges across study programs within the same university. This policy provides students with the freedom to take courses from other study programs, thus broadening their horizons and skills beyond their primary field of study. This community service project aims to explore the impact of this policy on student career competency. The method used was observation and interviews with students who had the opportunity to participate in the cross-study program exchange program. The results of the community service program indicate that flexibility in choosing courses across study programs not only improves academic ability but also students' interpersonal skills and adaptability. Thus, the internal exchange policy across study programs can be an effective strategy in improving students' preparation for facing the challenges of an increasingly dynamic workplace.